2019
DOI: 10.4102/aosis.2019.bk158.10
|View full text |Cite
|
Sign up to set email alerts
|

Drives towards research productivity: International trends

Abstract: Introduction 2 Approach followed 4 The policy process (including language in education) 5 Policy implementer appointments 12 Policy fatigue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This group includes countries like China [ 26 , 27 ] and Russia [ 28 ] that are simultaneously embracing neo-nationalism and autocratic control of higher education. While education researchers have argued that academic freedom has, at least in part, facilitated research production, the evidence behind these claims is mostly anecdotal [ 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This group includes countries like China [ 26 , 27 ] and Russia [ 28 ] that are simultaneously embracing neo-nationalism and autocratic control of higher education. While education researchers have argued that academic freedom has, at least in part, facilitated research production, the evidence behind these claims is mostly anecdotal [ 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have discussed the hypothesized link between research production and economic growth [ 7 ]. Some researchers [ 29 ] also have suggested that research production increases when scholars can research in the atmosphere of academic freedom, but to the best of our knowledge, none have tested the link empirically. Prior literature suggests several reasons research production might increase when scholars enjoy academic freedom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Lawrence (2002) notes that the pressure to publish may lead to unethical authorship practices and other academic misconduct. To that end, some researchers may engage in unethical behaviour and become co‐authors, even without substantial contribute to a written piece; produce an abundance of articles based on a modest dataset; use students' data instead of conducting their own studies; or compromise quality of the research process at the expense of getting data fast (Niemczyk & Rossouw, 2019).…”
Section: Research Findingsmentioning
confidence: 99%
“…The same situation is reflective of other external funding sources that provide financial support with specific return expectations. Scholarly literature (e.g., Carvalho & Diogo, 2017; Niemczyk & Rossouw, 2019) showed that the increase in institutional financial autonomy often comes at a price of relinquishing some control to financial supporters. Because academic researchers often require financial support for their projects, they must comply with specific criteria outlined in the call for funding, which may not align with researchers' research plans or preferences.…”
Section: Closing Remarksmentioning
confidence: 99%
See 1 more Smart Citation